A SYNTACTIC ANALYSIS OF THE ENGLISH NOUN PHRASE (A STUDY AT THE FIFTH SEMESTER OF ENGLISH DEPARTMENT FACULTY OF TEACHER TRAINING AND EDUCATION UNIVERSITY OF MUHAMMADIYAH MAKASSAR) - Junaid Junaid (-)
This study was intended to find out: (1) the students’ ability to construct the English Noun Phrase; (2) the causes of inaccuracy to construct English Noun Phrase. This study applied descriptive design. The samples of this study consisted of 40 students of the fifth semester of English Department. The data of this study were collected through the test. The data were analyzed by using descriptive statistics. Depending on the statistical results, the findings revealed that the students used 32 forming patterns of Noun Phrase which were covered in accuracy and inaccuracy construction. Those kinds of Noun Phrase patterns were identifier, adjective, noun modifier, quantifier, preposition phrase, participle clause, using conjunctions, and indefinite clause that all of the patterns were headed by Noun. The higher percentage of students’ accuracy to construct Noun Phrase was the pattern of identifier+Head, i.e., 27.4% meanwhile the higher percentage of students’ inaccuracy to construct Noun Phrase was the pattern of quantifier+Head, i.e., 17.6%. Besides, it is found that the causes of inaccuracy which are made by students in constructing Noun Phrase were classified into 11 categories, i.e., misused of identifier, misused of quantifier, misused of noun, omission of identifier, misordering, misused of plural, misused of singular, misformation, misused of word choice, omission of relative pronoun, and misused of adjective. The higher percentage of inaccuracy in constructing noun phrase was misused of singular, i.e., 17.4%.